SnTe nanomaterial decorated over graphene nanosheet for robust OER activity. (10th September 2022) - Manzoor, Sumaira; Nisa, Mehar Un; Abid, Abdul Ghafoor; Abdullah, Muhammad; Mersal, Gaber A. M.; Ibrahim, Mohamed M.; Taha Hamida, Taha Abdul‐Muhaimin; Ashiq, Muhammad Naeem
Summary: Hydrogen production via electrocatalytic water splitting has fascinated great attention because of its eco‐friendly nature and will be used as a renewable energy resource for the next decade. Despite marvelous efforts, we report the novel GO/SnTe nanocomposite fabricated via a simple chemical reduction approach for electrocatalytic water splitting. All the synthesized electrocatalysts are analyzed via different techniques. Furthermore, the electrochemical performance of fabricated electrode material employed on fluorine‐doped tin oxide was investigated with linear sweep voltammetry, cyclic voltammetry, chronoamperometry, and electrochemical active surface area to analyze the kinetics mechanism, active sites, and stability of the material using 1.0 M potassium hydroxide. The electrochemical result of the nanocomposite indicates a remarkable overpotential of 226 mV at 10 mA cm −2 current density with a Tafel slope of 53 mV dec −1 . Also, the nanocomposite has a 1.55 V lower onset potential vs reversible hydrogen electrode, and high stability of 180 hours. All these characteristics suggest that the electrocatalyst has potential for the oxidation reaction. Abstract : OER mechanism with Tafel slope values of fabricated materials.